Effect of FNS Incorporation on the Properties of Ternary Blended Cement Containing Blast Furnace Slag and Fly Ash - Min Jae Kim; Eon Sang Park; Woong Ik Hwang; Won Jung Cho (Advances in Materials Science and Engineering, 2022)
This study aims to assess the properties of ternary blended concrete in terms of mechanical performance and resistance to chemical attack. Specimens consisted of concrete and paste having a water to binder ratio of 0.45 made with ordinary Portland cement, pozzolanic materials, and ferronickel slag. Results on compressive strength at l80 days of curing showed that ternary blended concrete with ferronickel slag was 8% to 18% higher than for OPC. For splitting tensile strength and flexural strength, however, there was no such trend. Durability was examined in terms of resistance to rapid chloride penetration, carbonation, and sulfate attack. Ternary mix showed always-higher resistance against chloride penetration and sulfate attack while being more susceptible to carbonation due to the lower pH of the cement matrix. In addition, all ternary mixes exhibited lower heat of hydration compared to OPC and binary mixes with pozzolanic materials showed the lowest heat evaporation. Furthermore, from the results of XRD analysis, identical hydration products were found irrespective to the binder, while a significant change was observed on the portlandite peak. Overall, results showed that the incorporation of ferronickel slag affected positively the properties of concrete.